PENGARUH KUALITAS RESTORAN TERHADAP KEPUASAN PELANGGAN DAN REKOMENDASI PELANGGAN PADA RESTORAN CHINESE FOOD GUILIN SURABAYA - Shella Karlina Gonaldy; Fitri Novika Widjaja; Juliani Dyah Trisnawati (Perpustakaan Universitas Surabaya, 2018)
Abstract - The purpose of this study is to determine whether the quality of the restaurant has a affect to customer satisfaction or customer recommendation in Guilin chinese food restaurant Surabaya. The quality of restaurant is measured through the experience of eating perceived by customer in the restaurant as a whole. This study was analyzed using multiple ordinary least square (OLS)regression, binary logistic regression, and sobel test via the Statistical Package for Social Sciences (SPSS) 18.0 for windows.The results of this study found that restaurant service, physical atmosphere and overall quality has a positive and significant impact on restaurant quality. As well as the quality of the restaurant has a positive and significant impact on customer satisfaction. From customer satisfaction comes up the customer recommendation, where satisfied customers will be willing to recommend Guilin chinese food restaurant Surabaya to others. Thus, the results of the study support the concept of the theory about the impact of restaurant quality to customer satisfaction or customer recommendation.